DETERMINAN YANG MEMPENGARUHI CONTINUANCE INTENTION PENGGUNAAN E-WALLET DANA MENGGUNAKAN MODEL TECHNOLOGY CONTINUANCE THEORY (TCT) - Harum Dio Dwilestari (JUSS (Jurnal Sains dan Sistem Informasi), 2024)
Dana is one of the digital wallet service providers in Indonesia which was launched in 2018. Since its launch, Dana has had 10 million users, and has even been able to penetrate the top 3 digital wallet applications with the most monthly active users. However, in September 2020, the use of Dana decreased from 42% to 40%. This study aims to determine the factors that determine the intention tocontinous usage of Dana, especially in Jambi City. The method used in this study uses the Technology Continuance Theory (TCT) and analysis methods using sem-pls. Data is collected based on Dana users in Jambi City who have made transactions using Dana. The result of this research is that attitude and satisfaction are factors that directly influence the intention to sustain the use of funds. And theconfirmation variable is the key for service developers to keep funds in line with expectations.